Organic system evaluation of cassava varieties in the humid tropics of South India: agronomic, nutritional, quality, economic and soil health indicators - G. Suja; J. Sreekumar; S. J. Harishma; G. Byju; S. S. Veena; M. N. Sheela; S. Sunitha; A. N. Jyothi; D. Jaganathan; N. Ravisankar; C. S. Sooraj (Organic Agriculture, 2026)

Evaluation of dose-dependent hematotoxic effects of celastrol on human blood cells in vitro - Gayathri Hemant; Kurnegala Manikanta; Somanathapura K. NaveenKumar; Chandrashekar Tejas; Mysuru L. Sumedini; Kunthurumole S. Prashanth; Kabburahalli Sunitha; Kempaiah Kemparaju; Kesturu S. Girish (Toxicology Letters, 2026)

Multifunctional antimicrobial action of copper-chitosan nanocomposites against phytopathogens: Linking structure, function and plant immunity - Mummineni Sunitha; N.S. Pankaja; J. Mahadeva; Umashankar kumar; Vyamasani Shravani; Priyadharshini Venkatesan; S. Supriya; K.B. Bharathi; K.B. Sneha (Physiological and Molecular Plant Pathology, 2026)

Sarocladium spinificis: a first report as a causal organism of sheath rot in rice - Bharathi K.B.; Narayanareddy A.B.; Sanath Kumar V.B.; Denesh G.R.; Ashoka K.R.; Kitturmath M.S.; Varshitha S.; Sneha K.B.; Mummineni Sunitha; Akash Bevanur; Supriya S.; Sanju Jalli; et al. (Phytoparasitica, 2026)

Physics-Guided Deep Learning with Bayesian Optimization for Enhanced River Streamflow Prediction - D. Suresh; M. Sahaya Sheela; Pamarthi Sunitha; S. Gopalakrishnan (Water Resources Management, 2026)

Optimizing Water Productivity in Cassava Production: Comparative Water Footprint of Drip and Furrow Irrigation in Humid Tropics of India - S. Sunitha; A. U. Akash; J. Suresh Kumar; R. Saravanan (Irrigation and Drainage, 2025)
Efficient irrigation strategies are essential for optimizing water use in cassava production. This study evaluated the water footprint of cassava under five irrigation regimes—drip irrigation at 100%, 80% and 60% of crop evapotranspiration (ETc), furrow irrigation, and rainfed conditions—using field data from 2008 to 2012 validated with 2021–2023 data from humid tropical India. The crop ETc showed a decreasing trend, peaking at 378.8 mm in 2008–2009 and reaching its lowest value (307.6 mm) in 2021–2022. Drip irrigation at 100% ETc significantly reduced water use and blue water dependency compared to furrow irrigation, which exhibited high inefficiencies due to surface evaporation and runoff. The blue water usage under furrow irrigation (7200 m 3 in 2021–2023) was reduced to 2065 m 3 with drip irrigation. This efficiency resulted in higher cassava yields, with drip irrigation at 100% ETc achieving the highest yields (45.5 ± 7.3 t ha −1 in 2008–2012 and 46.7 ± 3.5 t ha −1 in 2021–2023), surpassing furrow (~26%–27% lower) and rainfed (~59% lower) conditions. Drip irrigation also led to the lowest total water footprint (80.9 ± 7.0 m 3 t −1 ), representing a 65% reduction compared with furrow irrigation and a 28% reduction compared with rainfed conditions (112.2 m 3 t −1 ). These findings provide crucial insights for sustainable cassava intensification.

Analysis of manoeuvring delay at urban unsignalized intersections under mixed traffic conditions using mathematical and RNNs models - Borigarla Barhmaiah; V. Sunitha; S. Moses Santhakumar (Innovative Infrastructure Solutions, 2025)

OsHV-1 Promoter-driven Transgene Expression in Bivalve Cells: An In Vitro Study with an EGFP-tagged Oncogenic H-RasV12 - Soumya Balakrishnan; Ambadi Kannan Maliyekkal Sajeevan; R. Namitha; M. R. Sunitha; A. Muneer; I. S. Bright Singh; Jayesh Puthumana (Environmental Management, 2025)

The role of TLRs (microbe recognition receptor) in gastric cancer: An update - Saade Abdalkareem Jasim; Sumaya Ayad Abdulrazzaq; H. Malathi; Suhaib Iqbal; Gaurav Sanghvi; E. Yulchiev; Subhashree Ray; S. Sunitha; Jawad Kadhim Ahmed; Ahmed Hussein Zwamel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Retraction notice to “Photocatalytic degradation of organic synthetic dyes and textile dyeing waste water by Al and F co-doped TiO2 nanoparticles” [Environ. Res. 206 (2022) 112492] - K. Ancy; M.R. Bindhu; Jeslin Sunitha Bai; Mansour K. Gatasheh; Ashraf Atef Hatamleh; S. Ilavenil (Environmental Research, 2025)

Evaluating geostatisical approaches and their integration with pedotransfer functions for estimating the spatial distribution of cation exchange capacity - Farag M. A. Altalbawy; Merwa Alhadrawi; Ashok Kumar Bishoyi; Subbulakshmi Ganesan; Aman Shankhyan; S. Sunitha; Anita Devi; Rajashree Panigrahi; Rubyat Alam (Environmental Monitoring and Assessment, 2025)

The role of VEGF in vascular dementia: impact of aging and cellular senescence - Neetu Agrawal; Muhammad Afzal; Nawaid Hussain Khan; Subbulakshmi Ganesan; Mukesh Kumari; S. Sunitha; Aniruddh Dash; Kavita Goyal; Brajgopal Kushwaha; A. Rekha; Mohit Rana; Haider Ali (Biogerontology, 2025)

Advancing Water Quality Assessment and Monitoring with a Robust Stacked Ensemble Method - Manisha. S. Babu; S Sreelakshmi; Vinod Chandra. S. S; V. Sunitha; E. Shaji (Water Resources Management, 2025)

Optimizing management interventions against Sclerotium rolfsii Sacc. On elephant foot yam (Amorphophallus paeoniifolius (Dennst.) Nicolson) in India - S.S. Veena; J. Sreekumar; M.L. Jeeva; G. Byju; G. Suja; S. Sengupta; C. Thangamani; Padmakshi Thakur; Ashish Narayan; Pradnya S. Gudadhe; S. Sunitha (Crop Protection, 2025)

Genetic enhancement of reproductive stage drought tolerance in RPHR-1005R and derivative rice hybrids through marker-assisted backcross breeding in rice (Oryza sativa L.) - N. Sravanraju; P. Beulah; V. Jaldhani; P. Nagaraju; A. S. HariPrasad; P. Brajendra; N. Sunitha; R. M. Sundaram; P. Senguttuvel (Molecular Biology Reports, 2024)

Socioeconomic Changes Based Climate Training for Agricultural Application Using Deep Learning Model - M. Sunitha; M. Durairaj; A. Rajalingam; Siti Khalidah Mohd Yusoff; S. Hari Chandra Prasad; S. N. Lakshmi Malluvalasa; Ajmeera Kiran (Remote Sensing in Earth Systems Sciences, 2024)

Ustilaginoidea virens, an emerging pathogen of rice: the dynamic interplay between the pathogen virulence strategies and host defense - Sunil Kumar Sunani; Prasanna S. Koti; N. C. Sunitha; Manoj Choudhary; B. Jeevan; C. Anilkumar; S. Raghu; Basana Gowda Gadratagi; Manas Kumar Bag; Licon Kumar Acharya; Dama Ram; Bishnu Maya Bashyal; et al. (Planta, 2024)

Role of surface and sub-surface ocean parameters on cyclonic storms over Arabian Sea in the recent decades - A. Amasarao; P. Sunitha; S. R. Rao; K. Chandra sekhar; B. Mmame (Natural Hazards, 2024)

Predictive power of YREMs and BLUPs for selecting superior genotypes in perennial crops: A black pepper case study - Mundagodu S. Shivakumar; Nagenahalli C. Sunitha; Hosahalli J. Akshitha; Koryampalli V. Saji; Sasikumar B. Pillai (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Revisiting population genetics with new genomic resources in dolichos bean (Lablab purpureus L. Sweet): an orphan crop - Vinayak Spoorthi; S. Ramesh; N. C. Sunitha; C. Anilkumar; M. S. Vedashree (Genetic Resources and Crop Evolution, 2024)

Arctic–midlatitude–tropics interactions in January 2020: linkages to precipitation extremes over Indian region - S. D. Sanap; M. Mohapatra; D. R. Pattanaik; S. Sunitha Devi; Satendra Kumar; A. Kashyapi (Meteorology and Atmospheric Physics, 2024)

Focused identification of germplasm strategy (FIGS): a strategic approach for trait-enhanced pre-breeding - N. C. Sunitha; M. D. Prathibha; R. Thribhuvan; B. M. Lokeshkumar; P. S. Basavaraj; H. C. Lohithaswa; C. Anilkumar (Genetic Resources and Crop Evolution, 2024)

The water footprint of root and tuber crops - S. Sunitha; A. U. Akash; M. N. Sheela; J. Suresh Kumar (Environment, Development and Sustainability, 2023)

Advances in integrated genomic selection for rapid genetic gain in crop improvement: a review - C. Anilkumar; N. C. Sunitha; Harikrishna; Narayana Bhat Devate; S. Ramesh (Planta, 2022)

Metabolite Effect on Angiogenesis: Insights from Transcriptome Analysis - P. Sunitha; Kesavan R. Arya; Achuthsankar S. Nair; Oommen V. Oommen; Perumana R. Sudhakaran (Cell Biochemistry and Biophysics, 2022)

Yield Estimation of Cassava Using SIMCAS Model Over the Major Cassava Growing Regions in India - Divya K. Lekshmanan; Raji Pushpalatha; V. S. Santhosh Mithra; S. Sunitha; James George; M. Velmurugan; P. Ashok; N. V. Mhasker; K. D. Desai; R. Shiny; Gangadharan Byju (Agricultural Research, 2022)

Discovery of genomic regions associated with resistance to late wilt disease caused by Harpophora maydis (Samra, Sabet and Hing) in maize (Zea mays L.) - N. C. Sunitha; E. Gangappa; R. P. Veeresh Gowda; S. Ramesh; Sunil Biradar; Dharanendra Swamy; H. B. Hemareddy (Journal of Applied Genetics, 2022)

Genetic stock identification in Perna viridis (Linnaeus1758) from the Indian Peninsula by using microsatellite markers - P. R. Divya; Linu Joy; Sunitha Poulose; P. M. Elizabeth Jency; V. S. Basheer; A. Kathirvelpandian; Vindhya Mohindra; Kuldeep Kumar Lal (Molecular Biology Reports, 2022)

Impact of climate change on the yield of tropical root and tuber crops vs. rice and potato in India - Raji Pushpalatha; VS Santhosh Mithra; S Sunitha; James Goerge; M Nedunchezhiyan; K Mamatha; P Ashok; Sheriful Alam; BK Saud; J Tarafdar; Surajit Mitra; Chandra Deo; et al. (Food Security, 2022)

Testing of Cassava (Manihot esculenta) Varieties for Climate Resilience Under Kerala (India) Conditions - Raji Pushpalatha; R. Shiny; Govindan Kutty; V. K. Dua; S. Sunitha; V. S. Santhosh Mithra; G. Byju (Agricultural Research, 2022)

Assessment of natural DNA methylation variation and its association with economically important traits in dolichos bean (Lablab purpureus L. Var. Lignosus) using AMP-PCR assay - H. Ajaykumar; S. Ramesh; N. C. Sunitha; C. Anilkumar (Journal of Applied Genetics, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Protective effect of (+)–catechin against lipopolysaccharide-induced inflammatory response in RAW 264.7 cells through downregulation of NF-κB and p38 MAPK - M. A. Sunil; V. S. Sunitha; Prasanthkumar Santhakumaran; Mohind C. Mohan; Midhun Sebastian Jose; E. K. Radhakrishnan; Jyothis Mathew (Inflammopharmacology, 2021)

Are genotypes’ single-year YREMs and BLUPs good predictors of their performance in future years? An empirical analysis in dolichos bean [Lablab purpureus (L.) Sweet var. Lignosus] - V. Spoorthi; S. Ramesh; N. C. Sunitha; P. V. Vaijayanthi (Genetic Resources and Crop Evolution, 2021)

Efficacy of Indolicidin, Cecropin A (1-7)-Melittin (CAMA) and Their Combination Against Biofilm-Forming Multidrug-Resistant Enteroaggregative Escherichia coli - Jess Vergis; S. V. S. Malik; Richa Pathak; Manesh Kumar; R. Sunitha; S. B. Barbuddhe; Deepak B. Rawool (Probiotics and Antimicrobial Proteins, 2020)

Role of enhanced synoptic activity and its interaction with intra-seasonal oscillations on the lower extended range prediction skill during 2015 monsoon season - S. Abhilash; R. Mandal; A. Dey; R. Phani; S. Joseph; R. Chattopadhyay; S. De; N. K. Agarwal; A. K. Sahai; S. Sunitha Devi; M. Rajeevan (Climate Dynamics, 2018)

Removal of heavy metals from tannery effluents of Ambur industrial area, Tamilnadu by Arthrospira (Spirulina) platensis - S. Balaji; T. Kalaivani; C. Rajasekaran; M. Shalini; S. Vinodhini; S. Sunitha Priyadharshini; A. G. Vidya (Environmental Monitoring and Assessment, 2015)

Viper venom-induced oxidative stress and activation of inflammatory cytokines: a therapeutic approach for overlooked issues of snakebite management - M. Sebastin Santhosh; M. Shanmuga Sundaram; K. Sunitha; K. Kemparaju; K. S. Girish (Inflammation Research, 2013)

An overview on genus garcinia: phytochemical and therapeutical aspects - M. Hemshekhar; K. Sunitha; M. Sebastin Santhosh; S. Devaraja; K. Kemparaju; B. S. Vishwanath; S. R. Niranjana; K. S. Girish (Phytochemistry Reviews, 2011)

Zooplankton community structure across an eddy-generated upwelling band close to a tropical bay-mangrove ecosystem - M. Rakhesh; A. V. Raman; C. Kalavati; B. R. Subramanian; V. S. Sharma; E. Sunitha Babu; Nanduri Sateesh (Marine Biology, 2008)

Ionic liquids as a reaction medium for lipase-catalyzed methanolysis of sunflower oil - S. Sunitha; S. Kanjilal; P. S. Reddy; R. B. N. Prasad (Biotechnology Letters, 2007)